PELAKSANAAN PENYIDIKAN TINDAK PIDANA PEMALSUAN SURAT TANAH DI WILAYAH HUKUM POLISI RESOR KOTA PEKANBARU - Lubis, Yohanna Elisabet (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Land rights based on the evidence of registration of land through land registration emergence soil letter is proof of land ownership . But today a lot going on forgery land made intentionally ( dolus ) to seize the property of others . However, the police play an important role in the crime of forgery of land , and therefore required the implementation of the investigation of criminal offenses of forgery of land in the resort city of Pekanbaru Police Law . The purpose of this thesis , namely : first , the implementation of the investigation of criminal offenses of forgery of land within the jurisdiction of Police Resort Pekanbaru City ; second , the obstacles in the implementation of criminal investigation of forgery of land within the jurisdiction of Police Resort Pekanbaru City ; Third , efforts are being made to overcome the obstacles in the implementation of criminal investigation of forgery of land within the jurisdiction of Police Resort Pekanbaru .This type of research is classified into types of juridical sociological research . Because in this study the authors directly conduct research on the location or place under study in order to give a complete and clear picture of the problem under study , the study was conducted in Pekanbaru City Police Resort . The data used is primary data , secondary data and data tertiary , data collection techniques using interviews and literature study .From the results of research and discussion, it can be concluded that the First , the implementation of the investigation of criminal offenses within the jurisdiction of Police Resort Pekanbaru not function as it should ; Second , obstacles in the implementation of criminal investigation of forgery of land within the jurisdiction of Police resort Pekanbaru is the presence of internal factors : the limited police personnel , lack of facilities , lack of traction on the police in handling criminal cases of forgery of land and external factors : the difficulty in find a letter comparison , and difficulty in calling witnesses ; Third , the efforts made to overcome obstacles in the implementation of the investigation of criminal offenses of forgery of land is on internal factors , namely the addition of personnel Pekanbaru City Police investigators , the addition of patrol cars and vehicles belonging to Pekanbaru City Police , the renewal of the things that are inventory and property for the execution of police duties , and the efforts of the external factors the coordination of the National Land Agency Pekanbaru to obtain a comparison of land documents , for witnesses who have died police call heir , and witnesses in pekanbaru bedomisi not to call the police and visited the residence of witnesses . Advice , implementation activities Pekanbaru Police investigation further enhanced ; party Pekanbaru City Police and the National Land Agency Pekanbaru to coordinate higher again ; types of land documents should be reduced to facilitate the implementation of the investigation of criminal offenses of forgery of land .Keywords : Investigation - Police - Crime - Counterfeiting Land Securities .